Influence of a home-based asthma health education program on quality of life and coping in parents of children with asthma. - Dolinar, Rose-Marie E. (University of Ottawa (Canada), 1997)
Asthma is the most common chronic illness of childhood and caring for a child with asthma can affect the parent's well-being and coping resources. The study examined the influence of a home-based asthma health education program on parental quality of life and coping. Hymovich's Contingency Model of Long-Term Care (Hymovich & Hagopian, 1992) guided the study which utilized a pretest-post-test control group design. Forty families were randomly assigned either to receive home-based asthma health education or booklet representing conventional care. Results of the three-month follow-up indicated improvement in the parent's perception of their child's asthma, as measured by the Caregiver Perception of Change (CPC) survey. Reduction in parental need for asthma information, reduction in parental concerns and increased use of coping strategies were observed, as measured by Hymovich's Parent Perception Inventory (PPI). Although no changes were detected by the Paediatric Asthma Caregiver's Quality of Life Questionnaire (PACQLQ), a significant correlation was seen between parental quality of life and parental coping.
Keywords: Health Sciences, Nursing.